Films as a Medium of Politics: Haider – Representation of Kashmir Politics in Shakespearean Tragedy (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
Films are an important medium for the portrayal and representation of politics. Kashmir, known for its natural beauty, became an essential destiny for Bollywood films. Many films were made in the 1960s with Kashmiri protagonists. Most of the films made in the 1960s era were apolitical, but in the post-1990s period, the films made on Kashmir reflected on the politics too. One of the films on Kashmir and its post-1990s is Haider, based on the Shakespearean play – Hamlet. This film was acclaimed by film critics as the bold job by the director to adopt the Shakespeare play in the context of Kashmir. This paper will analyze the story, dialogues, characters, and cinematography of the Film- Haider and explore how much it represents the politics of the 1990s in Kashmir. Using the content analysis approach, this paper will explore the relationship between the plot in the Shakespearean play and the political context of Kashmir.